The investigation of some physical properties and microstructure of Zn-doped hydroxyapatite bioceramics prepared by sol-gel method - Kaygili, O.; Tatar, C. (Springer, 2012)
In this study, the effect of Zn-dopant on the physical properties and microstructure of hydroxyapatite (HAP) bioceramics was investigated. The average crystallite size, phase composition and degree of crystallization of the pure hydroxyapatite and Zn-doped hydroxyapatite bioceramic samples prepared by sol-gel method were determined by X-ray diffraction method. It was seen that all the bioceramic samples were composed of the nanoparticles (29-46 nm). Fourier transform infrared spectroscopy was used to determine the functional groups in the samples. The dielectric properties of the bioceramics were investigated by dielectric impedance spectroscopy method, and the surface morphologies of them were analyzed using scanning electron microscopy technique. When the densities of the samples were measured by Archimedes method, it was seen that the densities of the samples increased with the increase of the molar ratio of Zn. The crystallization degree for all the samples dramatically decreased with the increasing content of the Zn dopant. With the increase of Zn to HAP, a change was observed in the degree of the crystallization, phase compositions, dielectric properties and microstructures of the samples.
Keywords: Hydroxyapatite; Bioceramic; Sol-gel method; Dielectric properties